Analisis Minat Membaca Melalui Buku Cerita Bergambar pada Peserta Didik Kelas III di SDN Bugangan 01 - Isworo, Diantri Nurjati; Rizky Esti Utami; Aries Tika Damayani; Suwarti, Suwarti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Reading interest is a strong motivation and active effort by individuals to engage in reading activities. This study aims to analyze the reading interest of grade III students at SDN Bugangan 01 through picture storybooks. The research employed is qualitative. The subjects of this study were grade 6 students, totaling 18 children. The primary data sources for this study were interviews and direct observations. The data collection methods included observations through questionnaires, interviews, and documentation. The data analysis technique involved data reduction, data presentation, and drawing conclusions. Based on the results of the data analysis, it can be concluded that the reading interest of grade 6 students is good. This conclusion is supported by the following indicators: the pleasure experienced when reading a good book, the strong need to read books, the interest in quality books, and the desire to read good books